2022
DOI: 10.1177/03915603221143419
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis prior to transrectal prostate biopsy in Croatia: A national survey

Abstract: Objectives: Transrectal ultrasound guided prostate biopsy (TRUSPB) is the standard of care for diagnosis of prostate cancer. Increased antibiotic resistance has led to the suspension of indication for fluoroquinolones use in prostate biopsy prophylaxis. Several classes of antibiotics have been recommended for routine use. Unequivocal consensus regarding antibiotic prophylaxis has not been made to date. The objective of the study was to assess the diversity of antimicrobial prophylaxis among Croatian urologists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…A recent study by Todorić et al (28) showed an increasing trend in enterococcal bacteremia in Croatia and a significantly higher This is another warning signal about the importance of adequately addressing fluroquinolone prescription habits in Croatia. A recent survey involving 12 urology departments in Croatia showed that fluoroquinolones were by far the most commonly prescribed class of antibiotics (accounting for 84% of prescriptions), and the authors have emphasized how the lack of uniform guidelines contributes to varying protocols, ultimately leading to a concerning escalation in antibiotic resistance (29).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Todorić et al (28) showed an increasing trend in enterococcal bacteremia in Croatia and a significantly higher This is another warning signal about the importance of adequately addressing fluroquinolone prescription habits in Croatia. A recent survey involving 12 urology departments in Croatia showed that fluoroquinolones were by far the most commonly prescribed class of antibiotics (accounting for 84% of prescriptions), and the authors have emphasized how the lack of uniform guidelines contributes to varying protocols, ultimately leading to a concerning escalation in antibiotic resistance (29).…”
Section: Discussionmentioning
confidence: 99%